Key technology research and engineering practice of speedy drivage with driving and bolting integration in soft surrounding rock - Hong WANG; Faquan LI; Xiaofeng ZHANG (Meitan kexue jishu, 2024)
The technology and equipment of speedy drivage with driving and bolting integration of soft surrounding rock is an urgent need for safe and efficient mining and intelligent construction of coal mines. Based on the background of mining roadway engineering with such a swelling soft rock and jointed soft rock , the development status of speedy drivage technology of bolter miner at home and abroad is sorted out, and three problems faced by speedy drivage of bolter miner under soft surrounding rock conditions are analyzed, including: disturbance control of surrounding rock by full width cutting, timely and efficient permanent support of soft surrounding rock, temporary support of lateral wall in speedy drivage of soft surrounding rock. Five key technologies for speedy drivage of soft surrounding rock are proposed, including: ① Low disturbance cutting technology. It mainly includes elliptical full-width cutting drum, pick arrangement optimization, cutting dynamics optimization, etc. ② Timely support technology to reduce the distance between coal face and permanent support for roof or lateral wall. This technology is based on the integrated technology of excavation and anchoring. Through the research of the multi-driller integral sliding platform integrating double cylindrical guidance, multi-link lifting, supporting oil cylinder top and bottom support, and follow-up gangue curtain protection, the distance between coal face and permanent roof support of the bolter miner is reduced from 2.5 m to 1 m, and the empty side distance is reduced from 3.5 m to 1 m. ③ Multi-dimensional collaborative support technology of soft surrounding rock. Considering the space-time synergistic effect between the bolt and anchor cable support parameters and the synergistic effect between the support body and the surrounding rock, the low-density strong bolt support is used to control the roof at the head, and the enhanced permanent support is implemented simultaneously at the rear. ④ Drilling anchor integration technology. It mainly includes bolt structure and mechanical properties, anchoring agent materials and pumping. ⑤ Coal side spraying temporary support technology. It mainly includes fast reaction high elongation spraying material, high proportion precision spraying pumping, irregular coal wall surface adaptive trajectory control, mine explosion-proof high-precision mechanical arm, spraying material matching supply, etc. Based on the above content, a controllable operation empty top distance bolter miner was developed and underground tests were carried out.The test shows that the equipment effectively shortens the empty roof distance and empty side distance, realizes the ' controllable ' empty roof distance, adapts to the speedy drivage of soft surrounding rock roadway, and doubles the excavation efficiency.